Implementasi Kebijakan Kesehatan Reproduksi - Alyas, Alyas (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
In order to analyze forms of the implementation of adolescent reproductive health policy and its impact through PIK KRR program at SMA Negeri 5 Makassar in Makassar. This research is a qualitative approach which used a case study. The data were collected through in-depth interview, observation, and documentation study. The data were analyzed by using qualitative data analysis conducted in three steps namely data reduction (data transcript), data presentation, and verification/conclusion. The results of the research indicate that the implementation adolescent reproductive health policy through PIK KRR program at SMA Negeri 5 Makassar in forms of promotion and socialization. Commitment improvement, education and training, quality improvement, and the implementation of administration and services of PIK KRR, have conducted according to the implementation guideline, but not yet optimal.